Antiquity as authority: Jesus and the patriarchs in the Gospel of John - Van Dyk, SL (2024)
Twice in John’s Gospel, Jesus is asked whether he is greater than the patriarchs Jacob and Abraham (μὴ σὺ μείζων εἶ …; John 4:12; 8:53). In each instance, the challenge directed to Jesus is contextually linked with his authority to offer eternal life (John 4:10, 13-14; 8:51-52). This study uses historical-critical exegesis to assess the Johannine author’s use of synkrisis to portray the authority of Jesus as greater than the authority of the patriarchs Jacob and Abraham. It is argued that the Johannine author adapts ancient aspects of authority, expressed through the re-articulation and transformation of patriarchal history, both in defence of Jesus and to determine the principal characteristics of Christ-followers and the boundaries of their communities. An assessment of the pervasiveness of two rhetorical arguments (the argument from antiquity alongside the argument from divine revelation) and three Hellenistic topoi (laudable ancestry/origins, great deeds, and communication with the divine realm) in Greco-Roman, late Second Temple and early Christian literature establishes the study’s conceptual foundation. A further evaluation of the authority of Jacob and Abraham in late Second Temple and post-Temple Jewish literature as well as early Christian literature determines the study’s contextual parameters. The Gospel’s depiction of Jesus as the pre-existent divine λόγος undergirds his depiction as one possessing authority superior to that of the patriarchs. The Gospel’s prologue and the testimony of John deliberately correlate the pre-existent divine identity of Jesus with his authority to grant eternal life. Three subsequent narratorial comparisons of Jesus with the patriarchs (John 1:1-51; 4:4-42; 8:31-59) establish his authority as one whose pre-existent divine origin surpasses the ancestral antiquity of Israel’s and Samaria’s ancestors, whose great deed of spiritual progeneration (John 1:12) surpasses the patriarchs’ progeneration of Israel, and whose revelation of God (John 1:18) surpasses their mediatorial roles.